Impact of Corporate Governance and Earning Management on Liquidity in Companies in the Tehran Stock Exchange - Kaveh Mehrani (Ph.D) (Shahid Bahonar University of Kerman, 2017)
The purpose of this study is to examine the joint effects of corporate governance and earnings management on stock liquidity, measured by trading volume. In this study, the data was collected from 154 companies listed in the Tehran Stock Exchange, in the period 2008 to 2015. The tests of hypotheses were carried out, using ordinary linear regression method. The results showed that the relationship between the two corporate governance variables, measured by the concentration rate of audit committee and the independence rate of directors, is significantly positive, and that the relationship between the other mechanism variable, called as ownership concentration rate and trading volume is significantly negative. Also, it was concluded that the relationship between earning management and trading volume is significantly negative. The earning management variable was measured by Defond and Park model, using difference between the realized working capital and the expected working capital to sustain current sales level. When we examined the joint effects of corporate governance and earnings management on stock liquidity, controlling the former to explore the potential effects of the latter, the result showed lack of significant relationship between earning management and trading volume.